Analysis of the principles of protection of confidential and private information to ensure the security of organizations and people - Meleshko, А. (Запоріжжя : 2024, 2024)
EN: Data protection is a set of methods and tools that ensure the integrity, confidentiality and availability of information in the face of natural or artificial threats, the implementation of which may cause damage to the owners and users of information. The basic principles of information and data protection include: 1. Network segmentation. Dividing the network into segments helps limit the spread of possible threats, thus preserving important resources and private data. 2. Protection against intrusions. Use of firewalls, detection systems and other means to detect and block unauthorised intrusions. 3. Protection against malicious software. Installing anti-virus software and other security tools aimed at detecting and removing malware. 4. Data encryption. The use of encryption to protect confidential information to prevent unauthorised persons from accessing it. 5. Password and identification security. Use strong passwords, two-factor authentication and other methods to prevent unauthorised access to systems. 6. Security audit. Conducting a systematic audit and vulnerability assessment to identify potential security issues and vulnerabilities.
Keywords: data protection; network segmentation; data encryption; password and identification security